Optimization of the cyclic In-plane response of reinforced concrete frames with infill masonry walls using a genetic algorithm - Folhento, Pedro Leonel Pamplona (2022)
A typical option in building construction is the use of reinforced concrete frame structures with infill masonry walls . The presence of infill walls in frame structures greatly influences the dynamic behavior of frame structures during seismic events. This wall usually does not have a structural role, being neglected in the design phase of building structures. Innumerous negative effects may arise from the neglection of this non-structural element in frame structures, namely, increased shear, energy, and ductility demands in the structure’s elements, torsional effects due to irregular height or plan distributions of the infill panels in buildings, out-of-plane failure of the walls projecting debris to the inside or outside of the buildings, etc. Hence, this work intends to study the in-plane cyclic behavior of reinforced concrete portal frame structures with infill walls . A numerical model is developed to replicate the quasi-static experimental response of reinforced concrete frames with infill walls specimens. To obtain an optimal response , the corresponding model’s parameters are calibrated through the use of a genetic algorithm . Results show that these algorithms can be a good option in calibrating the in-plane cyclic response of masonry infilled reinforced concrete frame structures. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.